2014
DOI: 10.3389/fpsyg.2014.01061
|View full text |Cite
|
Sign up to set email alerts
|

Using minimal human-computer interfaces for studying the interactive development of social awareness

Abstract: According to the enactive approach to cognitive science, perception is essentially a skillful engagement with the world. Learning how to engage via a human-computer interface (HCI) can therefore be taken as an instance of developing a new mode of experiencing. Similarly, social perception is theorized to be primarily constituted by skillful engagement between people, which implies that it is possible to investigate the origins and development of social awareness using multi-user HCIs. We analyzed the trial-by-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…A diachronic re-analysis of that original study by Froese et al (2014b) confirmed the expected relevance of the perceptual crossing paradigm for understanding the development of social perceptual awareness. It seems that the unfamiliar experimental setup forced the adults to implicitly re-learn the embodied skill of social perception, which may provide researchers with an opportunity to study a recapitulation of its original development in adults.…”
Section: Introductionmentioning
confidence: 69%
“…A diachronic re-analysis of that original study by Froese et al (2014b) confirmed the expected relevance of the perceptual crossing paradigm for understanding the development of social perceptual awareness. It seems that the unfamiliar experimental setup forced the adults to implicitly re-learn the embodied skill of social perception, which may provide researchers with an opportunity to study a recapitulation of its original development in adults.…”
Section: Introductionmentioning
confidence: 69%
“…The procedure involved first scrutinizing the phenomenological data (i.e., the rowers’ course-of-experience) to delineate the samples of behavioral data to be compared (i.e., various ways of experiencing the strokes give rise to various delineated sections within the race that will be further processed/compared). Such a subjectivity-based sampling method has been well developed in enactivist neuroscience (e.g., Rodriguez et al, 1999 ; Lutz et al, 2002 ; Lutz and Thompson, 2003 ; Froese et al, 2014a , b ). To our knowledge, this has not been used in the field of human movement or sports science.…”
Section: Methodsmentioning
confidence: 99%
“…This device puts two actors in situations where they have to move an avatar in a virtual environment populated by different entities (avatars of humans and various lures), visually empty but providing tactile stimulation at each encounter through the mouse used by the participants. Interestingly, what helps participants to succeed in finding each other, and subsequently to experience social connectedness, is the occurring co-regulation process they both perceived simultaneously at some instances (Froese et al, 2014a,b), regardless of the extent to which each actor was satisfied by the unfolding interaction, since they were not informed of their current effectiveness in the task. In agreement with the co-regulation requirement for interpersonal co-ordination emergence, most of the studies testing this regulation process have been experimental and have focused on the co-ordination within dyads, providing reiterated evidence of the interpersonal benefits related to co-regulation processes (Schmidt and Richardson, 2008).…”
Section: Hypothesis 2: Emergent Collective Behaviors Are Supported Bymentioning
confidence: 99%